Evaluation of inorganic and organic bone components after application of an apatite-coated Al2O3 implants as scaffolds for bone repair - Antonio Luiz Martins Maia Filho; Fabrício Pires de Moura do Amaral; Airton Abrahão Martin; Luís Eduardo Silva Soares (Brazilian Archives of Biology and Technology, 2014)
The aim of this work was to study the influence of uncoated and apatite-coated Al2O3 implants on bone regeneration after 30 days of surgery in New Zealand white rabbits. Twelve samples of Al2O3 implants were prepared and half of them (n = 6) were apatite-coated by the modified biomimetic method. Three experimental groups were tested as Group C - control, surgery procedure without cerami c implant, Group Ce - uncoated Al 2O3 implants (n = 6) and Group CeHA - apatite-coated Al2O3 implants (n = 6). The mineralization of the Al2O3 implants was analyzed in bone fragments using FT-Raman spectroscopy. Raman peaks at 959 cm-1 and 2940 cm-1 evaluated the inorganic and organic bone content, respectively. In vivo citotoxicity was analyzed using micronucleus test. Inorganic and organic content were higher in CeHA samples than in Ce and C (CeHA > Ce > C). FT-Raman spectroscopy showed that the higher the deposition of the organic matrix, more mineralization occurred. The micronucleus test showed that the uncoated and apatite-coated Al2O3 implants were non-cytotoxic and safe to in vivo applications.